Tecnologias de captação e aproveitamento de água de chuva para residências uni familiares - Kleindienst, Thiago Urbano Silva Von Gusseck [UNESP] (2015)
Water scarcity is becoming an increasing problem and more evident worldwide, rainwater utilization is characterized for being one of the simplest and cheapest solutions to preserve drinking water and is a known alternative technology and used to promote sustainability in buildings and reducing pressure on surface waters, it would also reduce runoff and can minimize flooding. The rainwater, while not potable may be used in potable water usage activities, and may thus saving 30 to 40% of potable water. In this work one can see the importance of the capture and use of rainwater (CAAC), bringing economy, to reduce consumption of potable water, reducing the problem of water shortage, and which methods and materials needed to cause its implementation. The work also promoted the characterization of rainwater in the city of Guaratinguetá (SP) and studied its potential use in public housing, calculating the volume needed for implementation of the tank and the cost to implement all rainwater utilization system, but because it is a region with a median rainfall index and the popular houses present an area of small water capitation, the result was not satisfactory. The cost for implementation was high and the financial return was well above average. The government should encourage and support more CAAC, as not thinking about the financial side is advisable to be widespread throughout the country, the benefits it can bring